SCAFFOLDING IN TEACHING LITERACY FOR ADULT LEARNERS IN TOURISM STUDY PROGRAM - I Putu Edi Sutrisna (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Teaching literacy for adult learners is challenging. The adult learners attending tertiary level education have certain unique learning characteristics that differs from regular teenager students. Finding out effective way in teaching them is very imporant. One of strategies that might be effective in teaching literacy in advanced level is scaffolding. It is believed that the scaffolinding is powerful tool in teaching lieteracy for adult learnenrs. Therefore, the present study administering qualitative method aimed at analyzing what scaffolding strategies used by the lecturers and finding out challenges faced by the lecturers in implementing the scaffolding strategies in teaching literacy for adult learners. The informants of study were three lecturers at Hindu Cultural Tourism Study Program of STAHN Mpu Kuturan Singaraja, Indonesia. The data collection were done by using content-validated interview guide and observation. The data analysis were done by using transcendental phenomenological research design. The result of study showed that the lecturers utilized three scaffolding strategies, namely conceptual scaffolding, strategic scaffolding, and metacognitive scaffolding. These scaffolding strategies were considered effective by the lecturers in the teaching literacy for adult learners. However, lecturers encountered difficulties in implementing scaffolding strategies in teaching literacy to adult learners. Those challenges were adult learners had multiple responsibilities that prevented them to be fully engaged into the learning activities outside the classroom, adult learners preferred learning activities that were practical rather than theoretical, and adult learners were resistant to changing their old learning habits.Â